Handbook of Research Ethics and Scientific Integrity 2019
DOI: 10.1007/978-3-319-76040-7_36-1
|View full text |Cite
|
Sign up to set email alerts
|

Ethics and Scientific Integrity in Biomedical Research

Abstract: Because it is directly implicated in major social issues, biomedical research is a paradigmatic field for working in ethics to cross-reference epistemic, social, and political issues. This chapter shows that the ethics and scientific integrity of biomedical research has grasped this challenge by placing the transversal concern of trust at the heart of its approach. This question of trust is put into perspective with that of trustworthiness, which is closely linked to it, and which is described as a way of thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…This was attributed to inequalities and power imbalances between developing and developed country partners, lack of effective communication, and lack of scientific integrity and questionable research practices. All these challenges are well documented in the literature ( Corbin et al, 2013 ; Katisi et al, 2016 ; Parker and Kingori, 2016 ; Walsh et al, 2016 ) and could result in loss of confidence and trust in collaborative research ( Moodley and Singh, 2016 ; Kretser et al, 2019 ; Coutellec, 2020 ; Singh et al, 2022 ). Trustworthiness is key to the success of biomedical research ( Kretser et al, 2019 ; Coutellec, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was attributed to inequalities and power imbalances between developing and developed country partners, lack of effective communication, and lack of scientific integrity and questionable research practices. All these challenges are well documented in the literature ( Corbin et al, 2013 ; Katisi et al, 2016 ; Parker and Kingori, 2016 ; Walsh et al, 2016 ) and could result in loss of confidence and trust in collaborative research ( Moodley and Singh, 2016 ; Kretser et al, 2019 ; Coutellec, 2020 ; Singh et al, 2022 ). Trustworthiness is key to the success of biomedical research ( Kretser et al, 2019 ; Coutellec, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…All these challenges are well documented in the literature ( Corbin et al, 2013 ; Katisi et al, 2016 ; Parker and Kingori, 2016 ; Walsh et al, 2016 ) and could result in loss of confidence and trust in collaborative research ( Moodley and Singh, 2016 ; Kretser et al, 2019 ; Coutellec, 2020 ; Singh et al, 2022 ). Trustworthiness is key to the success of biomedical research ( Kretser et al, 2019 ; Coutellec, 2020 ). Some researchers reported that they had at one stage encountered scientific misconduct in international collaborative research, and may be, that is why they did not trust that the provisions of the MTAs would be respected once samples are transferred across national boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…We base our anti‐paternalistic view on the notion that without truthfulness, editors are not trustworthy. Consequently, without trustworthiness, society at large cannot consent to biomedical science (Coutellec, 2020).…”
Section: “Silent” Retractions Violate Truthfulness and Trustworthinessmentioning
confidence: 99%
“…These epistemological challenges relate to the ethical issues of trustworthiness and trust [47]. Increasing efficiency in knowledge production is of little value if the research results cannot be verified or trusted.…”
Section: Concerns With Negative Effectsmentioning
confidence: 99%